Intimate intergroup contact across the lifespan. (19th October 2020) - Marinucci, Marco; Maunder, Rachel; Sanchez, Kiara; Thai, Michael; McKeown, Shelley; Turner, Rhiannon N.; Stevenson, Clifford
Abstract: Intergroup contact can be as casual as members of different groups walking past one another on the street or as intimate as developing cross‐group friendships or romantic relationships. To date, however, the majority of intergroup contact research has focused on examining the effects of contact through self‐report measures of interactions and friendships. While this research has made a substantial contribution to scientific understanding, less is known about how different forms of contact (casual vs. intimate) influence each other and are associated with outcomes across the lifespan. The present article focuses on intimate contact; a close and meaningful relationship or interaction with either an ingroup or outgroup member. We critically review the nature and consequences (good and bad) of intimate contact for children, youth and adults and for both majority and minority group members, focusing primarily on intimate intergroup contact. We also consider how intimate contact might be best measured in future research. Implications for research design, policy, and practice are considered.